Grace - Aronzon, Michal (Israel, 2012)
Grace is a woman from the Philippines who came to Israel 20 years ago in search of work, where she met and married a local man, and had three sons. After her divorce, she began to rediscover her sexuality and opened a beauty salon in Tel Aviv. Grace finds herself torn between her love for a woman who returned to the Philippines and her children's desire to be Israeli and serve in the IDF.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films